1976
DOI: 10.1159/000102489
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Evoked Potentials on Stimulation of the Human Pulvinar

Abstract: The distribution of the evoked cortical potentials recorded during stereotactic pulvinectomy is analyzed. The evoked cortical potential shows maximal amplitude in the precentral area, with decreasing amplitude in the parietal and anterior temporal area, and minimal amplitude in the occipital area. The pulvinar has been histologically considered to have dense connections with the parietal lobe and no connection with the frontal lobe. However, our results suggest that the pulvinar has a dense functional connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The fact that the lateral pulvinar has closer functional connection with the pre-central area rather than the parietal area, which had been thought to have dense fiber connection with the pulvinar, has been corre lated well with tire results of evoked potentials [7], This also supports the theory that the pulvinar may be related to motor function as well as sen sory function. However, it is still uncertain how the lateral pulvinar is functionally connected with the pre-central cortex.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The fact that the lateral pulvinar has closer functional connection with the pre-central area rather than the parietal area, which had been thought to have dense fiber connection with the pulvinar, has been corre lated well with tire results of evoked potentials [7], This also supports the theory that the pulvinar may be related to motor function as well as sen sory function. However, it is still uncertain how the lateral pulvinar is functionally connected with the pre-central cortex.…”
Section: Discussionsupporting
confidence: 65%
“…His tological studies show that this nucleus is mainly connected to the parietal and not to the frontal lobe [4,13]. We have already reported that the pul vinar is closely connected to the pre-central area as well as the parietal lobe, as shown by evoked potential studies [7].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation